2015
DOI: 10.1091/mbc.e15-07-0481
|View full text |Cite
|
Sign up to set email alerts
|

Ccq1-Tpz1TPP1interaction facilitates telomerase and SHREC association with telomeres in fission yeast

Abstract: Through characterization of ccq1 mutants that disrupt Ccq1-Tpz1TPP1 interaction, the authors establish that Ccq1-Tpz1TPP1 interaction contributes to optimal binding of the Ccq1-SHREC complex and is required for Ccq1 Thr93 phosphorylation and telomerase recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 28 publications
7
37
0
Order By: Relevance
“…Interestingly, truncations of the C-terminus to eliminate the coiled-coil motifs (lanes [1–441] and [1–500]) led to slight elongation of telomeres, implying that the C-terminus of Ccq1 is involved in negatively regulating telomere extension. This was unexpected as Ccq1 was thought to act solely as a positive regulator of telomerase and contradicted current knowledge ( 41 ). The series of Ccq1 truncations were relatively well expressed compared to full length Ccq1, except for the 1–424 and 1–400 fragments, which had significantly reduced expression ( Supplementary Figure S2B ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, truncations of the C-terminus to eliminate the coiled-coil motifs (lanes [1–441] and [1–500]) led to slight elongation of telomeres, implying that the C-terminus of Ccq1 is involved in negatively regulating telomere extension. This was unexpected as Ccq1 was thought to act solely as a positive regulator of telomerase and contradicted current knowledge ( 41 ). The series of Ccq1 truncations were relatively well expressed compared to full length Ccq1, except for the 1–424 and 1–400 fragments, which had significantly reduced expression ( Supplementary Figure S2B ).…”
Section: Resultsmentioning
confidence: 84%
“…Elimination of endogenous Ccq1 in strains expressing the Ccq1-Est1 chimera led to efficient telomerase recruitment and elongation of telomeres, indicating that endogenous Ccq1 is able to suppress the function of the Ccq1-Est1 chimera. Although Ccq1 is an abundant protein compared to Tpz1 ( 41 ), the negative regulation by endogenous Ccq1 was not simply caused by competitive occupation of Tpz1 against the Ccq1-Est1 chimera. Truncation analysis of endogenous Ccq1 showed that this elongation effect was also seen in strains with a C-terminal truncation of endogenous Ccq1 (amino acids 1–441) (Figure 3A : lane ccq1(1–441) in ccq1-est1 ), suggesting that a negative regulatory effect requires the Ccq1 C-terminus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the findings for ccq1Δ, the loss of H3 in mutants of CLRC is specific for TAS and not seen at tlh1 + ( Fig 3B). Ccq1 was further shown to interact with the HDAC Clr3, which is part of the repressor complex SHREC that also contains the Snf2-like nucleosome remodeler Mit1 ( Fig 3A) [9,21,22,29]. Mit1 and Clr3 have been associated with nucleosome positioning and turnover and prevent the formation of nucleosome-depleted regions within heterochromatin [21,[29][30][31].…”
Section: Ccq1 Maintains Nucleosome Stability By Recruiting Clrc and Smentioning
confidence: 99%
“…In humans and Schizosaccharomyces pombe, telomere protection is mediated by the shelterin complex, which consists of six subunits ( Fig 1A): Pot1 (hPOT1); Tpz1 (hTPP1); Poz1 (hTIN2); Rap1; Taz1 (hTRF1 and hTRF2) [1][2][3][4]. Fission yeast has an additional subunit Ccq1, which associates with shelterin via Tpz1 and is essential for maintaining telomere length through recruiting telomerase [2,[5][6][7][8][9][10]. When telomeres shorten to a critical size (after about 100 generations), cells undergo telomere crisis resulting in cell cycle arrest and cellular senescence [11].…”
Section: Introductionmentioning
confidence: 99%